(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: The objective of this work was to estimate the diversity of gastrointestinal (GI) parasite species, their prevalence, and risk factors in Black Bengal goats (BBGs) of Natore, Bangladesh. Materials and Methods: Fecal samples from randomly selected 260 BBGs were processed through Stoll’s ova counting method, floatation, and simple sedimentation method. Microscopy based identification of parasitic eggs, cysts, or oocysts was made. A semi-structured questionnaire-based data on host and management practices were collected from the owner. Data analysis was done using Statistical Package for Social Sciences. Results: The overall prevalence of GI parasites in BBGs was 65.4%, with an individual prevalence of 8.5% for Fasciola gigantica, 21.5% for Paramphistomum spp., 20% for Haemonchus spp., 34.2% for Strongyloides spp., 8.5% for Trichuris spp., and 9.2% for Eimeria spp. No significant effect of host age, gender, body condition, animal rearing system, or housing floor type was observed on parasitism. Animals of young age, female, poorly body-conditioned, living in a free-range system, and housed on a muddy floor had a relatively higher susceptibility to infection. Deworming had a significant impact on reducing the frequency of caprine GI parasitism. Conclusions: Despite the significant effect of anthelmintic, the elevated prevalence of GI parasites in BBGs suggests a critical need for developing effective strategies to prevent caprine parasitoses. J. Adv. Vet. Anim. Res., 10(1): 80–87, March 2023 http://doi.org/10.5455/javar.2023.j655